High-performance brazing of single crystal superalloys with Ni-Cr-Ta filler material - Zhenqian Lang; Taiyong Zou; Zheng Ye; Tao Wu; Wanli Wang; Jian Yang; Jihua Huang (Materials & Design, 2024)
High-performance joining especially brazing has been highly expected in the manufacture or maintenance of single crystal blades. In this paper, a Ni-40Cr-10Ta (at.%) alloy was developed as filler material for single crystal superalloys. High-performance brazing of DD5 superalloy was achieved. The joints brazed at 1260 °C contained an isothermal solidification zone (ISZ) with “γ + γ′” structure and an athermal solidification zone (ASZ) composed of γ, γ', γ/γ′-eutectics, TaCr2 and TaC. Unlike the conventional filler materials with melting point depressants of B and Si, the Ni-Cr-Ta filler material was free of B and Si, and thus the resulting joints contained no B-rich and Si-rich compounds and eutectics with low melting points, which enhanced the brazed joint performance. The tensile strength at 980 ℃ of the heat-treated joints reached 654 MPa, which is 88.5 % that of the base metal.